Isolation and Characterization of Wound Healing Compounds from Chloroform Extract of Binahong Leaves (Anredera cordifolia (Ten.) Steenis) - Rohani, Siti; Purwoko, Mitayani (Universitas Muhammadiyah Semarang, 2021)
The leaves of Binahong (Anredera cordifolia (Ten) Steenis) have been widely studied to have benefits and uses in various medical purposes, one of which is in the wound healing process. The existence of several active compounds contained in the leaves of the Binahong tree plant have an important role in wound healing, such as flavonoids, terpenoids, alkaloids, saponins, ascorbic acid and citrate compounds, these compounds are the targeted for further process of this natural product. The eminence of the extraction method that is used repeatedly and consistently to obtain pure compounds from Binahong leaves to be isolated is the one of topics discussed in this literature study. The perspective of implementation from liquid-solid extraction followed by liquid-liquid extraction using chloroform as a solvent is discussed comprehensively in this article. The identification of the isolation of compounds are able to conducted by implemented a thin layer chromatography (TLC) techniques, and for the further structural determination by UV, MS, FTIR, NMR spectroscopy and separation techniques using GC-MS. Respectively, the components are successfully to be identified and reported in previous research, for the following criteria that have been completed, some isolated active compound are purposed as the candidate for the wound healing agent. For the further application it is reasonable to implied these matters for some pharmaceutical products.